CYP27A1 expression is associated with risk of late lethal estrogen receptor-positive breast cancer in postmenopausal patients - Kimbung, Siker (Breast Cancer Res, 2020)
BACKGROUND: 27-Hydroxycholesterol (27HC) stimulates estrogen receptor-positive (ER+) breast cancer (BC) progression. Inhibiting the sterol 27-hydroxylase (CYP27A1) abrogates these growth-promoting effects of 27HC in mice. However, the significance of CYP27A1 expression on BC biology and prognosis is unclear. METHODS: Intratumoral CYP27A1 expression in invasive BC was measured by immunohistochemistry in two Swedish population-based cohorts (n = 645 and n = 813, respectively). Cox proportional hazards models were used to evaluate the association between CYP27A1 expression and prognosis. RESULTS: CYP27A1 was highly expressed in less than 1/3 of the tumors. High CYP27A1 expression was more frequent among high-grade tumors lacking hormone receptor expression and with larger tumor sizes. Over a median of 12.2 years follow-up in cohort 1, high CYP27A1 expression was associated with impaired survival, specifically after 5 years from diagnosis among all patients [overall survival (OS), HR(adjusted) = 1.93, 95%CI = 1.26–2.97, P = 0.003; breast cancer-specific survival (BCSS), HR(adjusted) = 2.33, 95%CI = 1.28–4.23, P = 0.006] and among patients ≥ 55 years presenting with ER+ tumors [OS, HR(adjusted) = 1.99, 95%CI = 1.24–3.21, P = 0.004; BCSS, HR(adjusted) = 2.78, 95%CI = 1.41–5.51, P = 0.003]. Among all patients in cohort 2 (median follow-up of 7.0 years), CYP27A1 expression was significantly associated with shorter OS and RFS in univariable analyses across the full follow-up period. However after adjusting for tumor characteristics and treatments, the association with survival after 5 years from diagnosis was non-significant among all patients [OS, HR(adjusted) = 1.08, 95%CI = 0.05–2.35, P = 0.83 and RFS, HR(adjusted) = 1.22, 95%CI = 0.68–2.18, P = 0.50] as well as among patients ≥ 55 years presenting with ER+ tumors [OS, HR(adjusted) = 0.46 95% CI = 0.11–1.98, P = 0.30 and RFS, HR(adjusted) = 0.97 95% CI = 0.44–2.10, P = 0.93]. CONCLUSION: CYP27A1 demonstrated great potentials as a biomarker of aggressive tumor biology and late lethal disease in postmenopausal patients with ER+ BC. Future studies should investigate if the benefits of prolonged endocrine therapy and cholesterol-lowering medication in BC are modified by CYP27A1 expression.